The structure of beta-diversity explains why the relevance of phytoindication increases under the influence of park reconstruction - Molozhon, Karina; Моложон, Каріна Олександрівна; Lisovets, Olena; Лісовець, Олена Іванівна; Kunakh, Olha; Кунах, Ольга Миколаївна; Zhukov, Oleksandr; Жуков, Олександр Вікторович (Oles Honchar Dnipro National University, 2023)
Urbanization causes the highest local extinction rates and often leads to the loss of the vast majority of native species. Plant communities are sensitive to urban expansion and are therefore indicators of human land use. A city park, part of which has undergone reconstruction, was studied. The study found the changes in ecological conditions caused by the reconstruction of a city park can be detected using phytoindication. The informativeness of phytoindication scales was shown to increase under conditions of anthropogenic load. The phytoindication scales are a reliable source of information for assessing the state of the vegetation cover of park plantations. The ecological regimes were assessed based on descriptions of the vegetation cover using Didukh's phytoindicative scales. The phytoindication approach allows to identify changes in ecological regimes that occur as a result of park reconstruction and to separate them from ecological regimes of natural origin. The study showed that the reconstruction of the park significantly affects the conditions of the park and the diversity of vegetation. The ratio of useful phytoindicative information compared to information noise in the structure of beta-diversity of the park's plantations increases significantly as a result of the park's reconstruction. The reconstruction of the park has led to changes in the spatial organization of the vegetation cover. The results obtained indicate a decrease in soil moisture as a result of the park's reconstruction. The park's reconstruction leads to a significant change in the light regime of park plantings, which leads to changes in the park's vegetation and soils. Reducing the density of plantations as a result of their pruning during the reconstruction process also decreases the amount of fallen leaves that form leaf litter. A significant increase in the variability of the moisture regime under the influence of the park reconstruction was found. The phytoindication revealed a decrease in the acidity of the soil solution as a result of the reconstruction. The changes in soil acidity are accompanied by an increase in phytoindication estimates of carbonate content in the soil. The observed increase in carbonate content estimates may be an artifact when representatives of another ecological group also have related ecological properties that can be misinterpreted as indicators of certain regimes. The phytoindication also revealed trends in the variability of microclimatic conditions in the park as a result of reconstruction. The reconstruction of the park leads not only to a change in the modal levels of ecological regimes, but also to the formation of specific patterns of their spatial distribution. The heterogenization of the ecological space under the influence of reconstruction has been established. This heterogenization is evident in the fact that areas with homogeneous vegetation cover are decreasing. The accuracy of the description of the spatial process was found to have decreased after the park reconstruction procedures. Smooth spatial structures of the park's vegetation cover without reconstruction are changing into rough spatial structures of the park after reconstruction. The park's reconstruction obviously disrupts the course of long-term processes that structure the vegetation cover, which leads to temporal and spatial desynchronization of the dynamics of ecological processes. The spatial variation of variables that indicate soil processes can best be described. In contrast, the phytoindication scales that indicate climatic factors are much less spatially structured. The best variogram model to describe the spatial process is also changing under the influence of reconstruction. The significant consequences of the park reconstruction are time variability and spatial heterogeneity of ecological processes. Урбанізація спричиняє найвищі локальні темпи вимирання та часто призводить до втрати переважної більшості місцевих видів. Рослинні угруповання чутливі до розширення міст і тому є індикаторами землекористування людиною. Досліджено міський парк, частина якого зазнала реконструкції. У результаті дослідження встановлено, що зміни екологічної обстановки внаслідок реконструкції міського парку можна виявити за допомогою фітоіндикації. Показано підвищення інформативності фітоіндикаційних шкал в умовах антропогенного навантаження. Достовірним джерелом інформації для оцінки стану рослинного покриву паркових насаджень є фітоіндикаційні шкали. Екологічні режими оцінювали за описом рослинного покриву за фітоіндикаційними шкалами Дідуха. Фітоіндикаційний підхід дозволяє виявити зміни екологічних режимів, що відбуваються внаслідок реконструкції парку, та відокремити їх від екологічних режимів природного походження. Дослідження показало, що реконструкція парку суттєво впливає на умови парку та різноманітність рослинності. Співвідношення корисної фітоіндикаційної інформації порівняно з інформаційним шумом у структурі бета-різноманіття насаджень парку внаслідок реконструкції парку значно зростає. Реконструкція парку призвела до змін у просторовій організації рослинного покриву. Отримані результати свідчать про зниження вологості ґрунту внаслідок реконструкції парку. Реконструкція парку призводить до суттєвої зміни світлового режиму паркових насаджень, що призводить до зміни рослинності та ґрунтів парку. Зменшення густоти насаджень внаслідок їх обрізання в процесі реконструкції також зменшує кількість опалого листя, що утворює листовий опад. Виявлено значне збільшення мінливості режиму зволоження під впливом реконструкції парку. Фітоіндикацією виявлено зниження кислотності ґрунтового розчину в результаті реконструкції. Зміна кислотності ґрунту супроводжується підвищенням фітоіндикаційних оцінок вмісту карбонатів у ґрунті. Спостережуване збільшення оцінок вмісту карбонатів може бути артефактом, коли представники іншої екологічної групи також мають споріднені екологічні властивості, які можуть бути неправильно витлумачені як показники певних режимів. Фітоіндикація також виявила тенденції мінливості мікрокліматичних умов парку внаслідок реконструкції. Реконструкція парку призводить не тільки до зміни модальних рівнів екологічних режимів, а й до формування специфічних закономірностей їх просторового розміщення. Встановлено гетерогенізацію екологічного простору під впливом реконструкції. Ця гетерогенізація проявляється в тому, що площі з однорідним рослинним покривом зменшуються. Встановлено, що точність опису просторового процесу знизилася після процедур реконструкції парку. Плавні просторові структури рослинного покриву парку без реконструкції змінюються на грубі просторові структури парку після реконструкції. Реконструкція парку вочевидь порушує перебіг багаторічних процесів структурування рослинного покриву, що призводить до часової та просторової десинхронізації динаміки екологічних процесів. Найкраще можна описати просторову варіацію змінних, які вказують на ґрунтові процеси. Навпаки, фітоіндикаційні шкали, які вказують на кліматичні фактори, набагато менш просторово структуровані. Найкраща модель варіограми для опису просторового процесу також змінюється під впливом реконструкції. Суттєвими наслідками реконструкції парку є часова мінливість та просторова неоднорідність екологічних процесів.
Структура бета-різноманіття пояснює, чому під впливом реконструкції парку зростає актуальність фітоіндикації
Keywords: recreation; рекреація; GIS; ГІС; innovation project; інноваційний проєкт; spatial ecology; просторова екологія; ecosystem transformation; трансформація екосистеми; plant ecology; екологія рослин; biometry; біометрія; human ecology; екологія людини